The Evolution of Black Women in Television: Mammies, Matriarchs and Mistresses - Cheers, Imani M. (Routledge, 2017)
This book seeks to interrogate the representation of Black women in television. Cheers explores how the increase of Black women in media ownership and creative executive roles (producers, showrunners, directors and writers) in the last 30 years affected the fundamental cultural shift in Black women’s representation on television, which in turn parallels the political, social, economic and cultural advancements of Black women in America from 1950 to 2016. She also examines Black women as a diverse television audience, discussing how they interact and respond to the constantly evolving television representation of their image and likeness, looking specifically at how social media is used as a tool of audience engagement.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Shaded Lives: African-American Women and Television - Smith-Shomade, Beretta E. (Rutgers University Press, 2002)
Since its invention, television has been one of the biggest influences on American culture. Through this medium, multiple visions and disparate voices have attempted to stake a place in viewer consumption. Yet even as this programming supposedly reflects characteristics of the general American populace, television-generated images are manipulated and contradictory, predicated by the various economic, political, and cultural forces placed upon it. In Shaded Lives, Beretta Smith-Shomade sets out to dissect images of the African American woman in television from the 1980s. She calls their depiction "binaristic," or split. African American women, although an essential part of television programming today, are still presented as distorted and deviant. By closely examining the television texts of African-American women in comedy, music video, television news and talk shows (Oprah Winfrey is highlighted), Smith-Shomade shows how these voices are represented, what forces may be at work in influencing these images, and what alternate ways of viewing might be available. Smith-Shomade offers critical examples of where the sexist and racist legacy of this country collide with the cultural strength of Black women in visual and real-lived culture. As the nation's climate of heightened racial divisiveness continues to relegate the representation of Black women to depravity and display, her study is not only useful, it is critical.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Real Housewives or Real Lies? New Constructions of "Housewives" on The Real Housewives of Atlanta - Shorter, Shavonne R. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
An old adage prescribed that “art imitates life.” If one believes this to be true, then it is plausible that entertainment is a source from which information about everyday life can be gleaned? Can U.S. television shows provide a looking glass into how Americans perform certain aspects of their lives? For a “real” look into how careers are performed, I have examined content from a reality television show which bears a title that implies something about the cast— the Bravo Network’s Real Housewives of Atlanta series. This show was chosen for two reasons. First, The Real Housewives of Atlanta is the most popular show among the “Housewives” franchise. Thus with each airing of the show, those who watch have the opportunity to learn more about the career aspirations, roles, and behaviors, of the cast members. Second, this is the only show within The Real Housewives franchise that features a primarily black cast. As such, the question emerges— can this show provide insight into the way black women construct their career roles? Another goal of this study is to determine how cast members construct notions of housewifery. Hence, throughout this chapter, readers will see that these women are not the typical “housewives,” rather they have reinvented what it means to be a housewife in the modern age.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Down Ass Bitch" in the Reality Television Show Love and Hip Hop: The Image of the Enduring Black Women and Her Unwavering Support of the Black Man - Alameen-Shavers, Antwanisha (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Within Spoken Soul, better known as Ebonics, the term down can be used as an adjective to describe a person that willingly yields a tremendous amount of support to another person. The “Down Ass Bitch” (DAB) is a controlling image of the black woman that calls for her unwavering support of the black man, even when it is pernicious to her best interest. In fact, we can see this in the black community on many levels: (1) from black women faithfully waiting years for men to be released from prison; (2) hiding domestic abuse or rape at the hands of black men for the sake of protecting the race; or (3) sexually exploiting our bodies for the financial benefit of black men. However, what is most interesting about this particular stereotype of the black woman being “down” for her man is that this is not an expectation that is asked of the black man. It is this author’s contention that the “Down Ass Bitch” is obsequious to the powers of black men— though she is portrayed as being strong, aggressive, and assertive. Essentially, the “Down Ass Bitch,” a highly celebrated image in the black community, is the black version of the submissive white woman, the Eurocentric construction of the idealized womanhood. Various controlling images of black womanhood— such as the mammy, the jezebel, and the welfare queen— served as justifications for the oppression of black women and have been discussed significantly by scholars.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Dehumanized and Empowered? Black Women, Reality Television, and Love and Hip Hop Atlanta - Bennett, Patrick; Griffin, Rachel Alicia (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In recent years, scripted television has been joined by a more “realistic” look into peoples’ lives— reality television. Reality television claims to give viewers an unmediated glimpse into how real people live. The “realness” of reality television invokes controversy by providing a voyeuristic and potentially exploitive look into people’s lives. As the genre has matured, shows that offer insight into communities that are systemically underrepresented have become common. Indicative of this trend are shows that depict the lives of African Americans and opportunistically exploit representations of black culture for drama, ratings, and profit. One network that has taken considerable advantage of this is VH1— first, with the success of Flavor of Love and its spinoffs, then more recently with shows such as Basketball Wives and Love and Hip Hop. In fact, the excessive amount of fighting among Black women on Basketball Wives led to a boycott of the show, which prompted creator Shaunie O’Neal to promise less violence in its next season. Akin to Basketball Wives , Love and Hip Hop Atlanta exemplifies the trend of exploiting black culture. As members of the black community, we find ourselves both intrigued and troubled by the implications of the show. Capturing the essence of our paradoxical interpretation of Love and Hip Hop Atlanta — as one of many reality television shows that simultaneously reproduces and challenges negative stereotypes about blackness— are contradictory headlines such as “The 21 Most Ratchet Women of Black Reality TV,” “How Reality TV has Changed our Daughters,” and “Wealthy Reality Stars Humanize Black Women.”
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

A Critical Analysis of Black Womahood in NBC's The Apprentice - Griffin Padget, Donyale R.; Allison, Donnetrice C. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Reality programs rose to prominence based on claims that the shows depicted “real life,” but in recent years many shows have come under fire for being anything but “reality.” Orbe (1998) suggests viewers are drawn to such programs based on the notion that they show “real people in everyday interactions,” and there is a certain level of “unpredictability that comes with reality.” However, what has become predictable and potentially problematic, over the past two decades, are the negative stereotypes associated with African American women on these programs. This skewing of reality is particularly significant when we consider the limited opportunities these shows provide viewers to witness the many facets of black womanhood. From the head-bobbing and finger-waving of Alicia Calaway on season two of the hit show Survivor to the on-and-off-air mudslinging between Kenya Moore and NeNe Leakes of Real Housewives of Atlanta fame, black women are portrayed as disloyal, bitchy, lazy, difficult to work with, and a threat to others.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The "Tyra Tyrade": Reinforcing the Sapphire Through Online Parody - Patton, Tracey Owens; Snyder-Yuly, Julie (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Tyra Banks, supermodel and producer, is the creator of the reality show America’s Next Top Model ( ANTM ), which is now in its twenty-second cycle, and features contestants who present themselves to a panel of judges for modeling critique. ANTM has been nominated for twenty-nine awards, including the GLAAD Media Award and Image Award, and the show has received five awards in 2009 from the Teen Choice Award and the Director’s Guild of America Award. Further, ANTM is currently shown in over 120 countries. The winner of each cycle receives a featured spread in a magazine, a modeling contract with a prominent agency, and a $100,000 modeling contract from a cosmetics company. In 2005, however, there was an infamous episode— dubbed the “Tyra Tyrade,” —where Tyra Banks yelled at a contestant whom she had just eliminated from the show. This episode was parodied more than any other ANTM episode, with the penultimate parody shown on a 2007 episode of Family Guy (a primetime cartoon television show with millions of viewers each week), where Tyra turns into a lizard and eats the model. While this episode is now nine years old, parodies from as recently as 2014 continue to live on and, as we argue, perpetuate negative stereotypes of black womanhood, particularly as related to the Sapphire mediated stereotype— loud, bossy, angry black woman. From the various interpretations of the “Tyra Tyrade,” it is clear that those who created the parodies covertly and overtly ventured into maintaining white supremacist stereotypes of black womanhood— where one is supposed to be beautiful, a jezebel, or a mammy, but not a Sapphire. Continuing the marginalizing mediated tradition, in almost every parody, the Tyra character becomes the object of ridicule for being “excessively black” and outside the parameters of her hegemonically prescribed role, because she demonstrated negative emotions resulting in an assertion of her power as the expert.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Is She Strong or Just a B!@*#? Discussion of Black Women's Anger in the Reality Show Bad Girls Club - Goldman, Adria Y. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
It is near impossible to have a discussion of black women in reality television without mentioning the infamous Angry Black Woman (ABW). In fact, some critiques have argued reality television is damaging for black women since many shows focus heavily on this character. 1 This stereotypical characterization of black women is long-standing, due largely to its constant inclusion in media messages. As noted in chapter one, audiences were first officially introduced to her in the 1920s as Sapphire Stevens from the Amos ‘n’ Andy Show ; and her character continued to resurface throughout the years, across several different genres. Despite the many time periods through which this image has traveled, the key characteristic of the Sapphire— her unexplainable anger and aggression— seem to resonate in many modern day images of black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Can't Have It All: An Analysis of Black Motherhood on Reality Television - Alford, Allison M.; Maxwell, Madeline M.; Jones, Ryessia D.; Morris, Angelica N. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
In this chapter we analyze three reality TV (RTV) shows whose main characters do not fit the old movie stereotypes of dark-skinned maternal Mammies, bossy, brown Sapphires or light-skinned sexy Jezebels. Many RTV shows with black cast members are falling back on such stereotypical representations. In contrast, the female characters we analyze are smart and sophisticated, and they live in multi-racial environments. Hence, the primary mediarelated question we address concerns how one slice of black motherhood is represented. The social question we address concerns the extent to which the character presentations actually point to social progress, with diverse symbols and meaning making of real life, or are they as artificial and stereotypical— perhaps in new ways— as the old portrayals?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Are Black Women Loud? Neoliberal and Postfeminist Protagonists in OWN's Televisual Sphere - Briceño, Mia E.; Estwick, Evene (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Jones’ comments reflect a general consensus among TV critics and viewers that: 1) the black women who command the most attention on reality television tend to portray stereotypical, Sapphire-like characters; 2) as audiences consume such portrayals, there is a consistent line of argument from producers that insists “pitting [black women] against each other” is expected or “what the people want;” and 3) black female reality TV stars are willing to indulge the Sapphire fantasy if it means they will be able to further a personal and/or professional agenda. These are important themes to interrogate, especially given the history of mass mediated representations of black Americans, as well as the present-day “evolution” of black characters and other characters of color on unscripted and scripted American television. However, because attention is primarily focused on arguably “negative” portrayals, there has not been much critical analysis of “alternative” or more nuanced portrayals of black women in the televisual sphere. This chapter represents an attempt to fill in some of that blank space by focusing attention on an underexplored and relatively new consortium of reality television programming that features black women who are defined by their roles as mothers and entrepreneurs.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

From 1990s Girl to Hip-Hop Wife: An Analysis of the Portrayal of Tiny as Black Mother in Reality Television - Jones, Ryessia D.; Jones, Johnny; Smith, Siobhan E. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
Although African-American women are still underrepresented in narrative television, reality television appears to be a site where one can find many portrayals of them. As other scholars have explained, the representations of African American women in reality television are usually negative, generally presenting them as loud, angry, and without “class.” However, there has been little research on the complicated relationships of black motherhood, black wifehood, and their portrayals on reality television. One black mother who illustrates this tense interaction is Tameka “Tiny” Harris, nee Cottle, formerly of the 1990s girl group Xscape, and star of two reality television programs— BET’s Tiny & Toya , and VH1’s T.I. and Tiny: The Family Hustle . Though both programs prominently feature Cottle, BET’s program constructs Tiny as an emotionally strong and pragmatically capable business woman who maintains the emotional health and financial stability of her family while her relational partner/husband, rapper Tip “T.I.” Harris, is serving time in prison. However, upon T.I.’s return home, The Family Hustle presents Tiny as having little business savvy and as overly permissive with their blended family. This is a dangerous portrayal, given that reality TV purports to disseminate some version of “reality” to its viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The God in Me: Faith, Reality TV, and Black Women - Egwu, Chetachi A. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The display of spirituality, faith and religion is not a new phenomenon among black women in the United States, nor is it new to the world of media. Africans came to the Americas with their own sense of spirituality and religion, and the awareness of a higher being became the mortar that bound the community together during the trials of enslavement and subsequent oppression. Not surprisingly, this legacy of worship continues to provide solace and strength, with black women at the helm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

High Tea, Church Hats, Pastor Wives, and Friendships: A Critical Race Feminism Analysis of Black Women in Preachers of L.A. - Whittington Cooper, Elizabeth (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The premise of the show revolves around six preachers in the Los Angeles area. They each pastor churches ranging from 3,500– 4,000 members; however, one pastor’s church has nearly 20,000 members (season 1: episode 1). A multitude of cameras follow the stories of each of the pastors’ lives, their relationships with each other, as well as their wives relationships with one another. The show has five black male preachers and one white male preacher. In season 1, all of the pastors— except for two— are married; one of the unmarried pastors is engaged to the mother of his child, and the other has a long-standing relationship with a female friend who frequently appears on the show. As viewers watch the show, they are given a glimpse into the world of evangelical preachers. Although at first glance the show seems to only focus on the men, the women provide an interesting glimpse at what it means to be a preacher’s wife, fiancée, or female companion. There were a total of eight episodes that aired over the course of two months. This chapter explores how black women and their friendships are portrayed on Preachers of L.A. — including the one white woman on the show. It also examines their discourse between one another— using critical race feminism to analyze the roles of these women as first ladies (a term used to describe the wives of pastors), their relationship with one other, and the conversations they have surrounding sex, marriage, relationships, and friendships. The chapter focuses on the first season of the show, which began in the fall of 2013. The show was later renewed for a second season, which began airing late summer 2014. This critique attempts to bring awareness to black women in the church and the discourse that perpetuates the stereotypes of black women on television. It also aims to initiate further conversations on various stereotypes— regardless of context— that have the potential to bear negatively on black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Graphic Blackness/Anime Noir: Aaron McGruder’s the Boondocks and the Adult Swim - Whaley, Deborah Elizabeth (Watching While Black, 2012)
Aaron McGruder’s “The Return of the King” (2006) is one of many of the artist’s controversial episodes, yet it stands out because of the criticism it received among mainstream media outlets and civil rights leaders. It was the ninth episode to air from his series The Boondocks, which is an anime show that airs on the Cartoon Network’s Adult Swim cable channel. McGruder presents the following scenario in “The Return of the King”: What if Martin Luther King Jr. (MLK) did not die after his April 4, 1968, shooting and instead awoke after being in a coma for thirty-two years?
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Nigger, Coon, Boy, Punk, Homo, Faggot, Black Man: Reconsidering Established Interpretations of Masculinity, Race, ans Sexuality Through Noah’s Arc - Cunningham, Mark D. (Watching While Black, 2012)
At best, our knowledge about the lives and experiences of Black gay men is limited to a series of stereotypes, snap judgments, and ridicule. In terms of television media product, this aforementioned knowledge has been packaged mostly within the framework of comedy: a red-leather-clad Eddie Murphy talking about the most effective ways to shield his ass from the gay male gaze in the 1983 HBO stand-up performance Delirious ; Damon Wayans and David Alan Grier’s effeminate film critics Blaine Edwards and Antoine Merriweather on the 1990s television variety show In Living Color ; fashionista panel members Miss J and Andre Leon Talley
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Prioritized: The Hip Hop (Re)Construction of Black Womanhood in Girlfriends and the Game - Lewis, Nghana (Watching While Black, 2012)
Why is it important that a Black woman created, wrote for, and co-produced¹ two highly-regarded television situation comedies that engaged a variety of Black women’s health issues while at the same time these issues were being reduced, simplified, or altogether ignored in mainstream American hip hop? Mara Brock Akil tacitly responded to this question when asked why four episodes of the third season of Girlfriends (2000–2008), the situation comedy she created and co-produced for UPN, addressed the HIV/AIDS crisis among Black women in America. “I have things I want to say,” explained Brock Akil, “about bridging television’s gap between
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Video Game History and the Fact of Blackness - Russworm, TreaAndrea M. (ROMchip, 2019)
Video games studies, including many of our most inspired written accounts of video game history, is very white. Stories about US video game pioneers, from engineers and designers to early adopters and arcade patrons, tend to be mostly about the white men who created, consumed, and periodically saved the industry. Even now that game history is on the verge of becoming as queer and ostensibly nonconformist as some aspects of its games and culture are theorized to be, these new avenues of critical investigation speak most directly to a queer mainstream that has always been constructed as white. Although there is much to be inspired by in the proliferation of emergent video game histories that are more gender-inclusive, trans, or so-called diverse, with few exceptions these progressive accounts still tend to be White. White. White. Black designers, players, blerds, and technocrats have been excluded from the canon of old and new video game histories in much the same way Frantz Fanon theorized that blackness functions as a fact: an outwardly defined pejorative social inscription that justifies its alienation and exclusion.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

“Embodiment and Subjectivity”: Intersectional Black Feminist Curatorial Practices in Canada - Joachim, Joana (RACAR: revue d'art canadienne / Canadian Art Review, 2018)
Dans le contexte de l’héritage canadien de colonialisme et de profond racisme, les musées ont contribué à l’oppression des Noir.e.s, des communautés de couleur et des peuples autochtones en gardant le silence ou en supprimant certaines histoires sous prétexte d’« objectivité ». Cet article examine les pratiques commissariales de deux femmes noires canadiennes, Gaëtane Verna, directrice et conservatrice en chef de la galerie d’art contemporain The Power Plant, et Andrea Fatona, commissaire indépendante, afin de situer le commissariat critique à l’intérieur de perspectives afroféministes intersectionnelles. En conformité avec une base conceptuelle fondamentale de ce féminisme, je soutiens que ce qui rend l’acte commissarial « critique » est la reconnaissance non seulement de la position qu’une personne occupe dans la société, mais aussi de celles dont elle ne fait pas toujours l’expérience. En examinant les pratiques de ces deux femmes, je mets au jour une riche histoire de l’art et du commissariat des Noir.e.s au Canada.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

The Limits of Feminism: Decolonizing Women's Liberation/Oppression Theory - Kuumba, Monica Bahati (Race, Sex & Class, 1994)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Ain't I a Woman Black Women and Feminism - hooks, bell (Routledge, 2015)
This landmark work of history and theory challenges every accepted notion about the nature of black women’s lives. Ain’t I A Woman examines the impact of sexism on black women during slavery, the historic devaluation of black womanhood, black male sexism, racism within the recent women’s movement, and black women’s involvement with feminism. hooks refutes the antifeminist claim that black women are not victims of sexist oppression nor in need of an autonomous women’s movement. She pushes feminist dialogue to new limits by claiming that all progressive struggles are significant only when they take place within a broadly defined feminist movement which takes as its starting point that race, class, and sex are immutable facts of human existence. bell hooks’ insight as a black woman and a feminist extends the scope of feminist theory and practice for us all, and marks the emergence of a revitalized feminism in the 1980s.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Black Looks: Race and Representation - hooks, bell (Routledge, 2015)
"In the critical essays collected in Black Looks, bell hooks interrogates old narratives and argues for alternative ways to look at blackness, black subjectivity, and whiteness. Her focus is on spectatorship--in particular, the way blackness and black people are experienced in literature, music, television, and especially film--and her aim is to create a radical intervention into the way we talk about race and representation. As she describes: 'The essays in Black Looks are meant to challenge and unsettle, to disrupt and subvert.' As students, scholars, activists, intellectuals, and any other readers who have engaged with the book since its original release in 1992 can attest, that's exactly what these pieces do"(Provided by publisher)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge Companions, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Exploring the Difficulties African-American Middle School Girls Face Enacting Computational Algorithmic Thinking over three Years while Designing Games for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Minor, Rachelle; Sun, Li (Computer Supported Cooperative Work, 2017)
Computational algorithmic thinking (CAT) is the ability to design, implement, and assess the implementation of algorithms to solve a range of problems. It involves identifying and understanding a problem, articulating an algorithm or set of algorithms in the form of a solution to the problem, implementing that solution in such a way that the solution solves the problem, and evaluating the solution based on some set of criteria. CAT is an important scaffolded on-ramp as students develop more advanced computational thinking capabilities and apply computational thinking to solve problems that are more constrained and require greater expertise. Supporting Computational Algorithmic Thinking (SCAT) is both a longitudinal between-subjects research project and a free enrichment program supporting and guiding African-American middle school girls over three years as they iteratively design a set of complex games for social change. This article explores Scholars' reflections about the difficulties they faced while using CAT capabilities as they engaged in collaborative game design for social change over those three years. We particularly focus on how these difficulties changed over the course of three years as well as new difficulties that emerged from year to year as Scholars become more expert game designers and computational algorithmic thinkers.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Exploring Collaborative Talk Among African-American Middle-School Girls in the Context of Game Design for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Saunders, Quimeka (Journal of Computing Sciences in Colleges, 2019)
Computer Science education research establishes collaboration among students as a key component in learning, particularly its role in pair programming. Furthermore, research shows that girls, an underrepresented population in computing, benefit from collaborative learning environments, contributing to their persistence in CS. However, too few studies examine the role and benefits of collaborative learning, especially collaborative talk, among African-American girls in the context of complex tasks like designing video games for social change. In this exploratory study, we engage 4 dyads of African-American middle school girls in the task of designing a video game for social change, recording the dyads' conversations with their respective partners over an eight-week summer game design experience during the second year of what has now become a six-year study. Qualitative analysis of dyadic collaborative discussion reveals how collaborative talk evolves over time in African-American middle-school girls.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Race and Media: Critical Approaches - Lopez, Lori Kido (New York University Press, 2020)
1. Racism and Mainstream Media / Lori Kido Lopez -- 2. Image Analysis and Televisual Latinos / Mary Beltrán -- 3. Visualizing Mixed Race and Genetics / Meshell Sturgis and Ralina L. Joseph -- 4. Listening to Racial Injustice / Dolores Inés Casillas and Jennifer Lynn Stoever -- 5. Branding Athlete Activism / Jason Kido Lopez -- 6. The Burden of Representation in Asian American Television / Peter X. Feng -- 7. Indigenous Video Games / Jacqueline Land -- 8. Applying Latina/o Critical Communication Theory to Anti-Blackness / Mari Castañeda -- 9. Asian American Independent Media / Jun Okada -- 10. Remediating Trans Visuality / Amy Villarejo -- 11. Intersectional Distribution / Aymar Jean Christian -- 12. Podcasting Blackness / Sarah Florini -- 13. Black Twitter as Semi-Enclave / Raven Maragh-Lloyd -- 14. Arab Americans and Participatory Culture / Sulafa Zidani -- 15. Diaspora and Digital Media / Lia Wolock -- 16. Disrupting News Media / Meredith D. Clark -- 17. Latinx Audiences as Mosaic / Jillian M. Báez -- 18. Media Activism in the Red Power Movement / Miranda J. Brady -- 19. Black Gamers' Resistance / Kishonna L. Gray -- 20. Cosmopolitan Fan Activism / Susan Noh.
Keywords: 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Exploring the Plurality of Black Women's Gameplay Experiences - Rankin, Yolanda A.; Han, Na-eun (Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems, 2019)
Few gender-focused studies of video games explore the gameplay experiences of women of color, and those that do tend to only emphasize negative phenomena (i.e., racial or gender discrimination). In this paper, we conduct an exploratory case study attending to the motivations and gaming practices of Black college women. Questionnaire responses and focus group discussion illuminate the plurality of gameplay experiences for this specific population of Black college women. Sixty-five percent of this population enjoy the ubiquity of mobile games with casual and puzzle games being the most popular genres. However, academic responsibilities and competing recreational interests inhibit frequent gameplay. Consequently, this population of Black college women represent two types of casual gamers who report positive gameplay experiences, providing insights into creating a more inclusive gaming subculture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Featuring Females: Feminist Analyses of Media - Cole, Ellen; Daniel, Jessica Henderson (American Psychological Association, 2005)
"Featuring Females analyzes the portrayals of women in a variety of outlets, including reality television shows, films, print and electronic news programming, magazines, video games, and commercial advertising. A highly esteemed group of scholars and researchers provides informed, original psychological study, and their thought-provoking findings address the ways in which aging, race/ethnicity, body image, gender roles, sexual orientation and relationships, and violence are treated in the media. Featuring Females is a diverse volume, exploring images and characterizations of women young and old and inspiring discussion of the effects that these representations have on girls, women, and society at large"--
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé; _À analyser; _À vérifier-Cinéma; _À vérifier-Télé

Gendered Play, Racialized Reality: Black Cyberfeminism, Inclusive Communities of Practice, and the Intersections of Learning, Socialization, and Resilience in Online Gaming - Richard, Gabriela T.; Gray, Kishonna L. (Frontiers, 2018)
In lieu of an abstract, here is a brief excerpt of the content: introduction While digital games hold promise for learning and socialization, emerging research and popular debates have critiqued inclusive access to these practices and literacies. This essay examines digital games for their potential to integrate diverse individuals and communities for learning and socialization, especially in online play and broadcasting of gameplay. For example, a level of cultural competency can be attained in well-developed games to overcome essentialist notions and assumptions about women and people of color. Using Black Cyberfeminism as a theoretical lens to make sense of players’ experiences, and Racialized Pedagogical Zones (RPZs) as an analytical frame to situate digital games’ entrenched ideologies of race and racism, we contend that games offer highly unproblematized depictions but have extreme potential for cultural competency. We further utilize Communities of Practice (CoP) as a frame for understanding and interrogating equitable access to community-supported collaborative learning and mastery within game culture, more broadly, and interest-driven guilds, clans, and affinity spaces, more specifically. In our extension of CoP, we integrate inclusive to highlight the resistive and resilient strategies employed by supportive communities for diverse women in addressing the systematic nature of oppression and power relations that undergird communities of practice, particularly in marked gendered spaces such as gaming. Marginalizing practices in game culture have become more widely publicized and understood in recent years, most notably because of high profile incidents of harassment. However, representations of women and racial or ethnic minorities by the gaming industry have also been problematic historically. For instance, since the 1980s video games have been critiqued for the hypersexualization of women and women are often the victims of misogynistic [End Page 112] vitriol, as the incidents around Gamergate have exposed. People of color are featured in largely stereotypical ways and are all but absent from the gaming industry. Queer gamers and gamers with dis/abilities are almost entirely absent and, when present, are not depicted fairly. This differential treatment appears to have a symbiotic relationship with the exclusion of marginalized players. As researchers have noted, Internet technologies and virtual communities operate in a manner that benefits privileged identities. These unequal power relations are accepted as legitimate and are embedded in the cultural practices of digital technology. Nevertheless, many gamers—most notably women—have resisted this perpetual state of inequity and the dominant narrative of power, control, and exclusion. Although some in gaming contend that these are not overt practices of exclusion, many players and scholars acknowledge the existence of symbolic exclusion, where those who are valued have the privilege to define legitimate practice and participation within gaming culture. The unequal power relations operating within the gaming community influence not only what gamers consume but also what they learn about themselves and others. Further, the racialized and gendered consumptive practices through gaming are often taken for granted. Commercial gaming culture is, with few exceptions, complicit in these exclusionary practices by continuing to design at a deficit, despite these increasingly apparent realities. But many gamers have begun to resist and challenge not only the imagery but also the practices that sustain white, masculine privilege within gaming and technology in general. While these practices have yet to reach a critical mass to disrupt the power structure operating within game culture as a whole, they exist counter to the mainstream and empower the marginalized operating within them. While the literature will provide an overview of these practices, our purpose is to privilege the resistance and resilience strategies of the marginalized to disrupt the traditional narrative while they empower themselves. We utilize Kimberlé Crenshaw’s framework of intersectionality to reflect on identity, recognizing that “the problem with identity politics is not that it fails to transcend difference, as some critics charge, but rather the opposite—that it frequently conflates or ignores intragroup differences.” We also want to caution that while we focus on players who have historically been the marginalized in gaming culture and game research, we recognize that men...
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Diffusion of Innovation Theory and Xbox Live: Examining Minority Gamers' Responses and Rate of Adoption to Changes in Xbox Live - Gray, Kishonna L. (Bulletin of Science, Technology & Society, 2012)
This article examines the response of minority gamers as they adopt new innovations in Xbox Live. Using diffusion of innovation theory, specific attention is given to gamers’ rate of adoption of the new Xbox Live environment, which was a recent update to the Xbox Live interface. By employing virtual ethnography, observations, and interviews reveal that gaming duration and gender are significant factors in identifying a gamer’s successful rate of adoption of the new innovation. Female participants reveal that Xbox Live intentionally targets males as the default gamer and enact changes based on their needs. The research concludes with a plea to Xbox Live to acknowledge minority gamers such as women to incorporate their needs within the decision-making process of new innovations.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave games in context, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Race, Gender, and Deviance in Xbox Live: Theoretical Perspectives from the Virtual Margins - Gray, Kishonna L. (Theoretical criminology series, 2015)
Race, Gender, and Deviance in Xbox Live provides a much-needed theoretical framework for examining deviant behavior and deviant bodies within one of the largest virtual gaming communities—Xbox Live. Previous research on video games has focused mostly on violence and examining violent behavior resulting from consuming this medium. This limited scope has skewed criminologists' understanding of video games and video game culture. Xbox Live has proven to be more than just a gaming platform for users. It has evolved into a multimedia entertainment outlet for more than 20 million users. This book examines the nature of social interactions within Xbox Live, which are often riddled with deviant behavior, including but not limited to racism and sexism. The text situates video games within a hegemonic framework deploying whiteness and masculinity as the norm. The experiences of the marginalized bodies are situated within the framework of deviance as they fail to conform to the hegemonic norm and become victims of racism, sexism, and other types of harassment.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Digital Diaspora: A Race for Cyberspace - Everett, Anna (SUNY Press, 2009)
Traces the rise of black participation in cyberspace.Deftly interweaving history, culture, and critical theory, Anna Everett traces the rise of black participation in cyberspace, particularly during the early years of the Internet. She challenges the problematic historical view of black people as quintessential information-age outsiders or poster children for the digital divide by uncovering their early technolust and repositioning them as eager technology adopters and consumers, and thus as coconstituent elements in the information technology revolution. She offers several case studies that include lessons learned from early adoption of the Internet by the Association of Nigerians Living Abroad and their Niajanet virtual community, the grassroots organizing efforts that led to the phenomenally successful Million Woman March, the migration of several historic black presses online, and an interventionist critique of race in contemporary video games. Ultimately, Digital Diaspora shows how African Americans and African diasporic peoples developed the necessary technomastery to ride in the front of the bus on the information superhighway.Anna Everett is Professor of Film and Media Studies at the University of California, Santa Barbara. Her books include Learning Race and Ethnicity: Youth and Digital Media; New Media: Theories and Practices of Digitextuality; and Returning the Gaze: A Genealogy of Black Film Criticism, 1909–1949.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé